THE INFLUENCE OF USING SHORT STORY ANIMATION ON STUDENTS’ VOCABULARY MASTERY - Syahla Nurhaliza; Sutrisno Sadji Evenddy; Ledy Nurlely (English Tadris Department, Tarbiyah and Teacher Training Faculty, Datokarama State Islamic University Palu, 2023)
This research purpose was to determine the influence of short story narrative text on students’ vocabulary mastery at the 10th grade of SMAN 1 PETIR. This research was done by true-experimental with random sampling. The population of this research was all of the first-grade high school students in Banten province, consisting of 350 students. The researcher used two classes, X MIPA 4 as the experimental and X MIPA 5 as the control class. Both classes consisted of 35 students. In obtaining the data, the researcher used multiple-choice questions as instruments. Try out was conducted as the first step to get the data. After conducting the tryout, the researcher gave a pre-test in both classes. The researcher gave the treatment in the experimental class using Short Story Animation as a media, and in the control class, the discussion method used a module. The result of the calculation by Independent T-test found that (0,002 < 0,005), which means the hypothesis alternative (Ha) is accepted. The effectiveness of using Short Story Animation Narrative Text can be seen in the ability obtained after the treatment.